Digestive complications that required additional surgical treatment after heart surgery - Montero, Hugo; Caviglia, Pablo; Cura, Leandro; Genta, Fernando (Cirugía del Uruguay, 2006)
Objectives: Analysing incidence of digestive complication subsequent to Heart surgery, in particular those cases requiring surgical treatment. The inciding variables.